2005
DOI: 10.1002/mop.20746
|View full text |Cite
|
Sign up to set email alerts
|

Compact printed ultra‐wideband slot antenna with a band‐notched operation

Abstract: The simulated relationship between the bandwidth versus RL differs by a few percent from the theoretical result, but follows a somewhat similar decreasing trend. One reason for the deviation obtained is due to the simple RLC circuit model used (lossless environments are assumed). The simulated results include lossy dielectric material as well as metal loss. However, the obtained result indicates that the suggested antenna has a performance that is close to the highest possible one expected from the RLC circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…In addition, the SRR structure exhibits not only magnetic resonance but also electric resonance induced by the dipole-like charge distribution along the incident electric field. Aydin et al have pointed out that closed SRR, i.e., the splits in the SRR are closed (see Figure 1(d)), will destroy the magnetic resonance but still keep the electric resonance [14,15]. Lots of experiments have demonstrated their predictions and shown that the first electric resonant frequency of SRR is higher than magnetic resonant frequency [14,15].…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the SRR structure exhibits not only magnetic resonance but also electric resonance induced by the dipole-like charge distribution along the incident electric field. Aydin et al have pointed out that closed SRR, i.e., the splits in the SRR are closed (see Figure 1(d)), will destroy the magnetic resonance but still keep the electric resonance [14,15]. Lots of experiments have demonstrated their predictions and shown that the first electric resonant frequency of SRR is higher than magnetic resonant frequency [14,15].…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Though it was built up by nonmagnetic conductors (like copper), it can yield negative effective magnetic permeability, which was introduced by Pendry et al in 1999 [13] and experimentally confirmed by Smith et al in 2000 [2]. The EM behavior of SRR can be described as follows: when the incident EM wave frequency is tuned to the magnetic resonant frequency band the EM wave propagation represents a nearly totally transmittance in this metamaterial, but when the EM wave frequency out of the magnetic resonant frequency band (except the electric resonant frequency band of SRR which induced by the dipole-like charge distribution [14,15]) the EM wave is nearly totally reflected. Naively, this feature of SRR may be used in EM engineering such as antennas, transmission lines system, frequency selective surfaces (FSSs), and filters for increasing their stopband/pass-band characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Those two resonances are due to the ground size and the ellipse axes as explained in [10]. The presence of a slot of total length approximately /2 at 5.8 GHz [11] creates the frequency notch in the return loss. The longer the slot length is the lower the frequency notch shifts.…”
Section: A Return Loss and Vswrmentioning
confidence: 98%
“…Some of them notched band antennas are introduced in literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In this circular notch antenna, with fractal tuning stub and ground slot plane with this type of structure one can achieve the notch filer.…”
Section: Introductionmentioning
confidence: 99%